2019
DOI: 10.2340/00015555-3293
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Squamous Cell Carcinoma Tumour Size is Associated with Sentinel Lymph Node Metastasis in a Cohort of 69 Patients

Abstract: SIGNIFICANCEAmong patients presenting a cutaneous squamous cell carcinoma, this study analyses the patient's and tumour's characteristics associated with metastasis in the first draining lymph node, called the "sentinel lymph node". The results show that a large tumour size is a risk factor for lymph node metastasis.Ten to fifty percent of high-risk cutaneous squamous cell carcinoma may potentially metastasize. However, the concept of sentinel lymph node biopsy remains controversial for cutaneous squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…After inclusion criteria were applied, the full text of 310 articles were assessed. Of these, 129 studies were included in final analysis (Figure 1). Study characteristics, including risk of bias, are described in eTable 1 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After inclusion criteria were applied, the full text of 310 articles were assessed. Of these, 129 studies were included in final analysis (Figure 1). Study characteristics, including risk of bias, are described in eTable 1 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 129 studies, 114 studies assessed risk factors, with a total of 137 449 patients and 126 553 tumors. Of these, 87 studies with 122 484 tumors were included in the random effects analysis risk ratio, and 62 studies with 116 958 tumors were included in analysis of incidence data. Treatment modality was assessed by 28 studies…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies evaluated the risk factors associated with positivity of SLNB results, but the findings differed among the studies, presumably because of the heterogeneity of the surgical indication for SLNB. The overall positive rate and false-negative rate in most of the previous studies were 5.4–14.6% and 0–5.7%, respectively [ 59 , 60 ]. Chabrillac et al reported that factors significantly associated with increased positivity of SLNB results were tumor size and poor tumor differentiation [ 59 ].…”
Section: Role Of Slnb In Skin Cancermentioning
confidence: 99%
“…The overall positive rate and false-negative rate in most of the previous studies were 5.4–14.6% and 0–5.7%, respectively [ 59 , 60 ]. Chabrillac et al reported that factors significantly associated with increased positivity of SLNB results were tumor size and poor tumor differentiation [ 59 ]. Another study showed that a tumor diameter ≥ 2 cm, tumor depth > 6 mm, or invasion into the subcutaneous fat, perineural invasion of nerves with a diameter ≥ 1 mm, moderate or poor histologic differentiation, lymphovascular invasion, and immunosuppression were associated with positive SLNB results [ 60 ].…”
Section: Role Of Slnb In Skin Cancermentioning
confidence: 99%
“…[7][8][9] There is a growing body of literature related to sentinel lymph node biopsy (SLNB) as a staging technique for highrisk cSCC. [10][11][12][13][14] Although most of these studies are retrospective and often report a mix of primary and recurrent tumors, they have provided valuable hypothesisgenerating data. However, additional research is needed to understand the optimal patient cohort for consideration of SLNB and the impact of SLNB results on cSCC outcomes.…”
mentioning
confidence: 99%